Identifying latent profiles of posttraumatic stress and major depression symptoms in Canadian veterans: Exploring differences across profiles in health related functioning. Issue 1 (30th July 2015) - Armour, Cherie; Contractor, Ateka; Elhai, Jon D.; Stringer, Maurice; Lyle, Gary; Forbes, David; Richardson, J. Don
Abstract: Posttraumatic stress disorder (PTSD) has been consistently reported as being highly comorbid with major depressive disorder (MDD) and as being associated with health related functional impairment (HRF). We used archival data from 283 previously war-zone deployed Canadian veterans. Latent profile analysis (LPA) was used to uncover patterns of PTSD and MDD comorbidity as measured via the PTSD Checklist-Military version (PCL-M) and the Patient Health Questionnaire-9 (PHQ-9). Individual membership of latent classes was used in a series of one-way ANOVAs to ascertain group differences related to HRF as measured via the Short-Form-36 Health Survey (SF-36). LPA resulted in three discrete patterns of PTSD and MDD comorbidity which were characterized by high symptoms of PTSD and MDD, moderate symptoms, and low symptoms. All ANOVAs comparing class membership on the SF-36 subscales were statistically significant demonstrating group differences across levels of HRF. The group with the highest symptoms reported the worst HRF followed by the medium and low symptom groups. These findings are clinically relevant as they demonstrate the need for continual assessment and targeted treatment of co-occurring PTSD and MDD. Highlights: We assessed the latent groupings of veterans responding to PTSD and MDD items. Resultant groupings were assessed in relation to health related functioning. A 3-class LPA model was found to provide the best fit to the data. Health related functioning was poorer is more symptomatic groupings.